Who Uses Electricity in Sub-Saharan Africa? Findings from Household Surveys - Kojima, Masami; Zhou, Xin; Han, Jace Jeesun; de Wit, Joeri; Bacon, Robert; Trimble, Chris (World Bank, Washington, DC, 2016)
Analysis of household expenditure surveys since 2008 in 22 Sub-Saharan African countries shows that one-third of all people use electricity. As expected, users are disproportionately urban and rich. In communities with access to electricity, lack of affordability is the greatest barrier to household connection. Lifeline rates enabling the poor to use grid electricity vary in availability, with six countries allowing 30 kilowatt-hours or less of electricity usage a month at low prices. Affordability challenges are aggravated by sharing of meters by several households -- denying them access to lifeline rates -- and high connection costs in many countries, made worse by demands from utility staff for bribes in some countries. Collection of detailed information on residential schedules enabled calculation of the percentage of total household expenditures needed for electricity at the subsistence and other levels. Affordability varied across countries, with grid electricity even at the subsistence level being out of reach for the poor in half the countries and even more so once connection charges are considered. Examination of the gender of the head of household shows that female-headed households are not disadvantaged in electricity use once income and the place of residence (urban or rural) are taken into account. However, female-headed households tend to be poorer, making it all the more important to focus on helping the poor for the goal of achieving universal access. Installing individual meters and subsidizing installation, encouraging prepaid metering so as to avoid disconnection and reconnection charges, reformulating lifeline blocks and rates as appropriate, and stamping out corruption to eliminate bribe-taking can all help the poor.